Nurses' practices and their influencing factors in palliative care - Xu, Yifan; Zhang, Shiwen; Wang, Jingrong; Shu, Zhiqun; Jing, Limei; He, Jiangjiang; Liu, Mengtian; Chu, Tianshu; Teng, Xiaohan; Ma, Yanan; Li, Shuijing (Frontiers in Public Health, 2023)
Background In 2017, the Chinese government launched a pilot project in palliative care, in which Shanghai was a pioneer. Nurses play a key role in palliative care services as they are the main providers improving the quality of services for patients and their families. However, little is known about practices and influencing factors in the field of palliative care from a nursing perspective in China. This is an original empirical study that has meticulously analyzed the interrelationship and intensity between practices and other factors among nurses in the initial stage of palliative care in primary healthcare institutions in Shanghai, China. Methods A descriptive-correlational study design was used to sample 2,829 eligible palliative care nurses by purposive sampling survey in 225 healthcare institutions in Shanghai, China. Descriptive analyses were performed using IBM SPSS 24.0 software. Structural equation modeling was applied to analyze the data by AMOS 20.0. Data were collected using the well-designed Knowledge, Attitudes, and Practices of Hospice Care (KAPHC) scale. Results The final model showed a good model fit. Self-efficacy directly influenced practices (β = 0.506, P < 0.01) and indirectly influenced practices (β = 0.028, P < 0.01) through intention. Subjective norm directly influenced practices (β = 0.082, P < 0.01) and indirectly influenced practices (β = 0.030, P < 0.01) through intention. Intention (β = 0.152, P < 0.01) and knowledge (β = 0.068, P < 0.01) directly influenced practices. Perceived susceptibility (β = −0.027, P < 0.01), perceived benefits (β = −0.017, P < 0.01), and perceived barriers (β = −0.014, P < 0.01) indirectly influenced practices through intention. Conclusion This study provided evidence of the associations of knowledge, perceived susceptibility, benefits, barriers, subjective norm, self-efficacy, intention, and practices among nurses concerning palliative care and interventions improving their actual work practices. Our findings revealed that self-efficacy, intention, and subjective norms greatly influenced practices. It is imperative to take interventions that focus precisely on self-efficacy, intention, and subjective norms to improve nurses' practices.